Ekranisasi Novel Surga yang Tak Dirindukan karya Asma Nadia ke dalam Film Surga yang Tak Dirindukan karya Sutradara Kuntz Agus - Huda, Nabila; Shomary, Sudirman; Andriyani, Noni (J-LELC: Journal of Language Education, Linguistics, and Culture, 2021)
Ekranization is a study that discusses the issue of casting a novel into a film. The problems of this research are: how is the process of ekranizationf the shrinking aspects in the novels and films of Surga yang Tak Dirindukan? How is the process of ekranization the additional aspects in the novel and film of Surga yang Tak Dirindukan? How is the process of ekranization the various aspects of change in novels and films of Surga yang Tak Dirindukan? This study aims to determine: the process of ekranization the shrinking aspects in the novel and film of Surga yang Tak Dirindukan; The process of ekranization the additional aspects in the novel and film of Surga yang Tak Dirindukan; The process of ekranization the various aspect of change from novels and films of Surga yang Tak Dirindukan. This research includes library research.This study uses a comparative descriptive method. Data collection techniques using hermeneutic techniques and documentation. The theory used is the theory of Eneste (1991). The results of the study: (1) In the aspect of shrinking, there are 61 data that occur in the elements of events, characters, and novel setting. Such as the absence of events from 3 novels, Adam charackter, and the boarding house setting in the film; (2) Additional aspects, there ara 40 data that occur on the elements of event, characters, and film settings. Such as the addition of scene 2, the character Sibil, and the background of the hospital roof in the film; (3) The aspect change various, there are 26 data that occur on the element of events, characters, and novel setting. Such as the depiction of event from 2 novel to scene 4 films, changes in the depiction of Arini’s character, and changes in the depiction of bedroom setting. The ekranization process causes shrinking, addition, and variation. This happens because of the differences in the media used in making novels and films, differences in the cultivation process, and differences in the enjoyment process.